FLORISTIC DIVERSITY OF SECONDARY FOREST IN THE EASTERN AMAZON, STATE OF AMAPÁ - Guimarães, José Renan da Silva; Carim, Marcelo de Jesus Veiga; Tostes, Luciedi de Cássia Leôncio; Costa Neto, Salustiano Vilar da (Floresta, 2016)
The increasing importance of secondary forests all over the world alerts us to the urgent need to understand the biophysical and social underlying factors that affect its regeneration after the abandonment of agricultural practices and natural disturbances. In the state of Amapá, studies related to the structure of secondary forests are still scarce. Therefore, this article aims to characterize the floristic composition and structure in two stretches of secondary forest in the eastern Amazon, state of Amapá. For the floristic and phytosociological study of tree species, 10 plots of 10 x 100 m (1.0 ha) were established: five plots in the community of São Francisco do Iratapuru and five plots in the community of Santo Antônio waterfall, totaling half a hectare (0,5 ha) in each area. In all plots, subjects with diameter at breast height (DBH) ≥ 5 cm were considered. In total, 1,183 subjects were sampled in the two stretches of forest. In stretch 01, 565 subjects belonging to 74 species, 55 genera and 33 families were recorded. In stretch 02, 618 subjects belonging to 26 species, 23 genera and 15 families were recorded. The Shannon diversity index (H'), estimated for stretch 1, was 3.52; and for stretch 2 (2.23). The two studied stretches, despite being registered at the same age, showed significant difference in the species richness, which is the major factor for diversity differences, resulting in low similarity between the studied forests.